On the rapid TeV flaring activity of <ASTROBJ>Markarian 501</ASTROBJ> - Mastichiadis, A.; Moraitis, K. (2008)
Aims: We investigate the one-zone SSC model of TeV blazars in the presence of electron acceleration. In this picture, electrons achieve their maximum energy as the acceleration saturates due to a combination of synchrotron and inverse Compton scattering losses. Methods: We solve the spatially averaged kinetic equations that describe the simultaneous evolution of particles and photons, obtaining the multiwavelength spectrum as a function of time. Results: We apply the model to the rapid flare of <ASTROBJ>Mrk 501</ASTROBJ> of July 9, 2005 as observed by the MAGIC telescope, and derive the relevant parameters for the pre-flare quasi-steady-state and the states during the flare. We demonstrate that a hard lag flare can be obtained with parameters well inside the range expected for this source. In particular, a high value of Doppler factor appears necessary.
Keywords: acceleration of particles; Astrophysics; galaxies: BL Lacertae objects: individual: Mrk 501; galaxies: jets; gamma rays: theory; radiation mechanisms: non-thermal; X-rays: galaxies